A comparison of density–modulus relationships used in finite element modeling of the shoulder. (April 2019) - Knowles, Nikolas K.; Langohr, G. Daniel G.; Faieghi, Mohammadreza; Nelson, Andrew J.; Ferreira, Louis M.
Highlights: Clinical resolution FEM accuracy is improved by site-specific modeling parameters. Comparison of the most commonly used relationships allow for a critical evaluation of the most accurate relationships. A computational methodology that directly compares FEM accuracy was used. Abstract: Subject- and site-specific modeling techniques greatly improve the accuracy of computational models derived from clinical-resolution quantitative computed tomography (QCT) data. The majority of shoulder finite element (FE) studies use density–modulus relationships developed for alternative anatomical locations. As such, the objectives of this study were to compare the six most commonly used density–modulus relationships in shoulder finite element (FE) studies. To achieve this, ninety-eight (98) virtual trabecular bone cores were extracted from uCT scans of scapulae from 14 cadaveric specimens (7 male; 7 female). Homogeneous tissue moduli of 20 GPa, and heterogeneous tissue moduli scaled by CT-intensity were considered. Micro finite element models (µ-FEMs) of each virtual core were compressively loaded to 0.5% apparent strain and apparent strain energy density (SEDapp ) was collected. Each uCT virtual core was then co-registered to clinical QCT images, QCT-FEMs created, and each of the 6 density–modulus relationships applied (6 × 98 = 588 QCT-FEMs). The loading and boundary conditions were replicated and SEDapp was collected and compared to µ-FEM SEDapp . When a homogeneous tissue modulus was considered in the µ-FEMs, SEDapp was best predicted in QCT-FEMs with the density–modulus relationship developed from pooled anatomical locations (QCT-FEM SEDapp  = 0.979µ-FEM SEDapp  + 0.0066, r 2  = 0.933). A different density–modulus relationship best predicted SEDapp (QCT-FEM SEDapp  = 1.014µ-FEM SEDapp  + 0.0034, r 2  = 0.935) when a heterogeneous tissue modulus was considered. This study compared density–modulus relationships used in shoulder FE studies using an independent computational methodology for comparing these relationships.